2019
DOI: 10.2217/fon-2019-0346
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Afatinib and Osimertinib in Patients with EGFR Mutation-Positive Non-Small-Cell Lung Cancer: Updated Analysis of the Observational Giotag Study

Abstract: Aims: Overall survival (OS) and updated time to treatment failure (TTF) analysis of patients with EGFR mutation-positive (Del19, L858R) non-small-cell lung cancer who received sequential afatinib/osimertinib in the real-world GioTag study. Patients & methods: Patients had T790M-positive disease following first-line afatinib and received osimertinib treatment (n = 203). Primary outcome was TTF. The OS analysis was exploratory. Results: Median OS was 41.3 months (90% CI: 36.8–46.3) overall and 45.7 months (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 27 publications
5
74
0
2
Order By: Relevance
“…However, this result should be interpreted with caution since the number of patients in this group was small [27]. Another retrospective study on the efficacy of second-line osimertinib is the GioTag study [55], a global observational study, assessing as first end-point the time on treatment. They observed that subsequent use of afatinib and osimertinib, in patients who had developed T790 M mutation, led to a median overall survival of 41.3 months (90% CI: 36.8-46.3) overall and 45.7 months (90% CI: 45.3-51.5) in patients with Del19-positive tumors (n = 149).…”
Section: Expert Opinionmentioning
confidence: 94%
“…However, this result should be interpreted with caution since the number of patients in this group was small [27]. Another retrospective study on the efficacy of second-line osimertinib is the GioTag study [55], a global observational study, assessing as first end-point the time on treatment. They observed that subsequent use of afatinib and osimertinib, in patients who had developed T790 M mutation, led to a median overall survival of 41.3 months (90% CI: 36.8-46.3) overall and 45.7 months (90% CI: 45.3-51.5) in patients with Del19-positive tumors (n = 149).…”
Section: Expert Opinionmentioning
confidence: 94%
“…92 An interim analysis has demonstrated a median OS of 41.3 months (90% CI: 36.8-46.3) overall and 45.7 months (90% CI: 45.3-51.5) in patients with Del19-positive tumors (n=149). 93 The 2-year survival was 80% and 82%, respectively, for patients overall and those with Del19 tumors. 93 A key challenge of the second line use of osimertinib is to ensure that all patients who develop T790M-driven resistance are identified; this requires re-biopsy, and the widespread availability of sensitive T790M detection assays.…”
Section: Second-line Treatment Options For Nsclc Patients and The Neementioning
confidence: 96%
“…93 The 2-year survival was 80% and 82%, respectively, for patients overall and those with Del19 tumors. 93 A key challenge of the second line use of osimertinib is to ensure that all patients who develop T790M-driven resistance are identified; this requires re-biopsy, and the widespread availability of sensitive T790M detection assays. EGFR mutations can be analyzed in tumor biopsies and in cellfree plasma DNA from blood samples (liquid biopsy).…”
Section: Second-line Treatment Options For Nsclc Patients and The Neementioning
confidence: 96%
See 2 more Smart Citations